Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To solve the system of equations:
[tex]\[ \begin{array}{l} y = -5x + 3 \\ y = 1 \end{array} \][/tex]
we need to find the values of [tex]\(x\)[/tex] and [tex]\(y\)[/tex] that satisfy both equations simultaneously. Here are the steps to solve this system:
1. Substitute the value of [tex]\(y\)[/tex] from the second equation into the first equation:
Given [tex]\( y = 1 \)[/tex] from the second equation, we can substitute this value into the first equation:
[tex]\[ 1 = -5x + 3 \][/tex]
2. Solve for [tex]\(x\)[/tex]:
Rearrange the equation to isolate [tex]\(x\)[/tex]:
[tex]\[ 1 = -5x + 3 \implies -5x = 1 - 3 \implies -5x = -2 \][/tex]
Divide both sides by [tex]\(-5\)[/tex]:
[tex]\[ x = \frac{-2}{-5} = 0.4 \][/tex]
3. Determine the corresponding [tex]\(y\)[/tex] value:
From the second equation [tex]\( y = 1 \)[/tex], we already know that when [tex]\(x = 0.4\)[/tex], [tex]\(y\)[/tex] will be 1.
Therefore, the solution to the system of equations is:
[tex]\[ (x, y) = (0.4, 1) \][/tex]
Among the given options, the correct one is:
[tex]\[ (0.4, 1) \][/tex]
[tex]\[ \begin{array}{l} y = -5x + 3 \\ y = 1 \end{array} \][/tex]
we need to find the values of [tex]\(x\)[/tex] and [tex]\(y\)[/tex] that satisfy both equations simultaneously. Here are the steps to solve this system:
1. Substitute the value of [tex]\(y\)[/tex] from the second equation into the first equation:
Given [tex]\( y = 1 \)[/tex] from the second equation, we can substitute this value into the first equation:
[tex]\[ 1 = -5x + 3 \][/tex]
2. Solve for [tex]\(x\)[/tex]:
Rearrange the equation to isolate [tex]\(x\)[/tex]:
[tex]\[ 1 = -5x + 3 \implies -5x = 1 - 3 \implies -5x = -2 \][/tex]
Divide both sides by [tex]\(-5\)[/tex]:
[tex]\[ x = \frac{-2}{-5} = 0.4 \][/tex]
3. Determine the corresponding [tex]\(y\)[/tex] value:
From the second equation [tex]\( y = 1 \)[/tex], we already know that when [tex]\(x = 0.4\)[/tex], [tex]\(y\)[/tex] will be 1.
Therefore, the solution to the system of equations is:
[tex]\[ (x, y) = (0.4, 1) \][/tex]
Among the given options, the correct one is:
[tex]\[ (0.4, 1) \][/tex]
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.